Complexed Semiconductor Cores Activate Hexaniobate Ligands as Nucleophilic Sites for Solar‐Light Reduction of CO2 by Water. Issue 49 (4th November 2022) - Zhang, Guanyun; Wang, Fei; Tubul, Tal; Baranov, Mark; Leffler, Nitai; Neyman, Alevtina; Poblet, Josep M.; Weinstock, Ira A.
Abstract: Although pure and functionalized solid‐state polyniobates such as layered perovskites and niobate nanosheets are photocatalysts for renewable‐energy processes, analogous reactions by molecular polyoxoniobate cluster‐anions are nearly absent from the literature. We now report that under simulated solar light, hexaniobate cluster‐anion encapsulated 30‐Ni II ‐ion "fragments" of surface‐protonated cubic‐phase‐like NiO cores activate the hexaniobate ligands towards CO2 reduction by water. Photoexcitation of the NiO cores promotes charge‐transfer reduction of Nb V to Nb IV, increasing electron density at bridging oxo atoms of Nb‐μ‐O‐Nb linkages that bind and convert CO2 to CO. Photogenerated NiO "holes" simultaneously oxidize water to dioxygen. The findings point to molecular complexation of suitable semiconductor "fragments" as a general method for utilizing electron‐dense polyoxoniobate anions as nucleophilic photocatalysts for solar‐light driven activation and reduction of small molecules. Abstract : Remarkably rapid CO2 reduction by solar light and water is achieved using molecular analogs of metal‐oxide intercalated niobate nanosheets.